Global Forum: Spine Research and Training in Underserved, Low and Middle-Income, Culturally Unique Communities. (21st December 2016) - Brady, O'Dane; Nordin, Margareta; Hondras, Maria; Outerbridge, Geoff; Kopansky-Giles, Deborah; Côté, Pierre; da Silva, Sophia; Ford, Timothy; Eberspaecher, Stefan; Acaroğlu, Emre; Mmopelwa, Tiro; Hurwitz, Eric L.; et al.
Abstract : The World Spine Care (WSC), established by volunteers from 5 continents, is dedicated to providing sustainable, evidence-based spine care to individuals and communities in low and middle-income countries consistent with available health-care resources and integrated within the local culture. The research committee approves and oversees the WSC's collaborative research and training projects worldwide and serves to create a sustainable research community for underserved populations focused on preventing disability from spinal disorders. The purpose of this article is to describe 4 projects overseen by the WSC research committee and to discuss several challenges and specific facilitators that allowed successful completion of initiatives. These novel projects, which involved establishing spine surgery expertise and data collection in the WSC clinics and surrounding communities, all met their aims. This was achieved by overcoming language and resource challenges, adapting to local customs, and taking time to build mutual respect and to nurture relationships with local investigators and stakeholders.